Counseling on Balanced Nutrition to Youth at SMK Negeri 02 Dompu - Khatimah, Nur Husnul; Sutriawan, Sutriawan; Gufran, Gufran (AMK : Abdi Masyarakat UIKA, 2023)
Adolescence is an age that is vulnerable to various nutritional problems because, at the age of adolescence, the body experiences an accelerated growth and development process so it requires more energy. In addition, teenagers also like to follow changes in lifestyle and eating habits that are not necessarily healthy, giving rise to various nutritional problems in adolescents. This health education is carried out to encourage students to make positive behavior changes by balanced nutrition in their teens.ActivityCommunity service is carried out inKandai Satu Dompu Village, by conducting health counseling on balanced nutrition for adolescents at SMK Negeri 02 DOMPU. Counseling participants totaled 60 students. Counseling is carried out using the lecture method and audio-visual media to make it interesting and easier for students to understand the material and distribute posters on tips for maintaining a balanced nutritional pattern to increase students' knowledge and understanding of balanced nutrition in adolescents. Counseling received a good response and ran smoothly, the message conveyed was well received by students. This is evidenced by an increase in student's knowledge about balanced nutrition in adolescents, students understand the health problems caused by unbalanced nutrition. The hope is that the interventions that have been given can be applied by students in everyday life so that they can improve the nutritional status of adolescents.